Al-‘Amal Aṣ-Ṣāleh Wa Jazāuhu Fil Qur’anil Karīm: العمل الصالح وجزاءه في القرآن الكريم - Ishak Sofyan; Nabil Ahmed Tamam; Yogi Suparman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2020)
This study aims to define and reward good work in the Qur'an, in order to explain the verses of good work, to study and to act through its punishment in this world and in the hereafter. This study follows the inductive and analytical approach by tracking the words of scientists in the interpretation contained in the bellies of the books of interpretations and related references, and then collecting them, classifying them, presenting them, and analyzing them, according to its terms and parts. This study proved that every good work has its reward in this world and the hereafter, which the Holy Quran brings on the face of it, and then refers to the prophet's statement in the meanings of the verse.